2023
DOI: 10.1088/1742-6596/2426/1/012030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cation distribution on structural and mechanical properties of Y3+ substituted Co-Zn spinel ferrites nanoparticles.

Abstract: Yttrium (Y3+) substituted Co-Zn spinel ferrite nanoparticles with compositional formula Co0.9Zn0.2YxFe1.9-xO4 (x = 0.0, 0.015, 0.030, 0.045, 0.06) were synthesized by using sol-gel auto-ignition route. The structural and mechanical properties of Co-Zn ferrites were tailored by the replacement of Fe3+ ions by Y3+ ions. Rietveld refined X-ray diffraction patterns of all the samples confirm the cubic spinel structure. Lattice parameter increases with the substitution of Y3+ ions which may be due to the difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…There are many published studies on the structure of spinel compounds, often as nanomaterials, in which both the ADPs and the inversion are modeled using data of much lower quality than in the present study. , Figure compares the room-temperature ADPs of ZnFe 2 O 4 obtained in the present study with the values published in the literature, as listed in the Inorganic Crystal Structure Database (ICSD) . Clearly, there are serious problems with many published structures; a lot of values are unreasonably high, with some of them deviating more than 300% from the values determined here.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…There are many published studies on the structure of spinel compounds, often as nanomaterials, in which both the ADPs and the inversion are modeled using data of much lower quality than in the present study. , Figure compares the room-temperature ADPs of ZnFe 2 O 4 obtained in the present study with the values published in the literature, as listed in the Inorganic Crystal Structure Database (ICSD) . Clearly, there are serious problems with many published structures; a lot of values are unreasonably high, with some of them deviating more than 300% from the values determined here.…”
Section: Resultsmentioning
confidence: 74%
“…The literature on Debye temperatures of spinel ferrites from the diffraction data is quite limited, and some of the published fits appear to be problematic. , The values obtained from diffraction are generally lower than those from IR or elastic constants, and this was postulated to be an artifact of using the Fd 3̅ m space group in structural refinements instead of the claimed true space group of F 4̅3 m . However, the average Debye temperatures found here are significantly higher than those previously determined from diffraction and in quite good agreement with those reported from IR, 569 K for ZnFe 2 O 4 , and elastic constants, which generally lie in the 450–700 K range for spinel ferrites. , This, in conjunction with our analysis establishing Fd 3̅ m as the true space and the poor agreement between the diffraction data and the model reported by Modi et al and Lakhani et al, points to the previous values reported from diffraction being inaccurate due to insufficient data quality or potentially varying defect structures.…”
Section: Resultsmentioning
confidence: 74%